Romanticism in the Poetry of Raz Mohammad Raz - Wahab, Abdul; Seemab, Naseebullah (sourcecoder, 2024)
In this article, the inlays are poems of Professor Raz Muhammad Raz have been taken. Raz Muhammad Raz is among the poets of South Pakhtunkhwa who have their own unique style. His individual style is built within the framework of romanticism, because intellectual rebellion is revealed in his poems. He breaks the traditional frameworks of Pashto poetry in terms of intellectual references and presents his thoughts in a philosophical context. This is a characteristic of Raz Muhammad Raz poetry and gives him uniqueness in Pashto poetry.